Mapping an antibody-binding site and a T-cell-stimulating site on the 1A protein of respiratory syncytial virus. - Nicholas, J A (1988)
A synthetic peptide modeled on residues 45 to 60 of the 1A protein of respiratory syncytial (RS) virus [1A(45-60)] was constructed and used for immunization of mice and rabbits. The immunoglobulin G fraction of the resulting rabbit antibody, purified on protein A-Sepharose, immunoprecipitated from RS-infected HEp-2 cells a protein with a molecular size of approximately 9.5 kilodaltons, which corresponds to the previously published molecular size of the 1A protein (Y. T. Huang, P. L. Collins, and G. W. Wertz, Virus Res. 2:157-173, 1985). To investigate the T-cell-inducing properties of 1A(45-60), six strains of mice were immunized and their popliteal lymph node cells were tested for proliferation upon restimulation with peptide in vitro. The lymph node cells of all six strains of mice were responsive to restimulation with 1A(45-60) and showed high- and low-responder strain variation. These peptide-primed lymph node cells also proliferated upon in vitro restimulation with RS virus-infected cells. Correlation of proliferation with interleukin 2 production suggested that the responding lymphocytes were T-helper cells. The antibody-binding and T-cell-stimulating sites of 1A were mapped by constructing a series of overlapping synthetic peptides and testing each for ability to react with antiserum prepared by immunization of BALB/C mice with free peptide 1A(45-60) or for ability to restimulate proliferation in 1A(45-60)-primed lymph node cells of BALB/C mice. Human antibody, obtained during confirmed RS virus infection, was similarly tested with the truncated peptides. Antibody-binding activity was reduced after truncation from the carboxy terminus, and a binding site was mapped to residues 51 through 60, the smallest peptide tested. T-cell-stimulating activity in mice was relatively resistant to truncation from the carboxy terminus and sensitive to truncation from the amino terminus. The smallest region which retained significant T-cell-stimulating activity mapped to residues 46 through 56. However, addition of the naturally occurring Cys at residue 45 and extension of the C terminus to residue 62 resulted in maximum T-cell-stimulating activity of the peptide. These data define both a T-cell epitope and a B-cell epitope of the 1A protein of RS virus and suggest that the carboxy terminus of 1A contains a B-cell epitope, involving residues 51 through 60, which is recognized during natural human infection.